1995
DOI: 10.1111/j.1944-9720.1995.tb00823.x
|View full text |Cite
|
Sign up to set email alerts
|

From Theory to Practice: How Do We Prepare Teachers for Second Language Classrooms?

Abstract: Major reform efforts in the field of teacher education have occurred during the past decade. This article provides a description of one institution's response to reform efforts within the context of a post‐baccalaureate second language teacher education program, which combines the preparation of foreign language and English as a second language (ESL) teachers. The description begins with a brief overview of the theoretical and philosophical foundations that guide practice within the program. These foundations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 26 publications
1
24
0
2
Order By: Relevance
“…Even though teachers' competence in the target language is a requirement to use CLT, researchers in the field (Crandall, 1999;Freeman, 1989;Tedick & Walker, 1995) have found that the education of EFL teachers tends to focus on theoretical pedagogical knowledge and on English language skills based on grammar, phonology, morphology, syntax, and lexicon of the language, and more recently in notions and functions. In this sense, it is not surprising that teacher education programs in Venezuela, for example, place a heavy emphasis on descriptive linguistics, i.e., the study of the language at the sentence level (Chaco´n, Alvarez, Brutt-Griffler, & Samimy, 2003), overlooking the social nature of language as a means of communication and interaction.…”
Section: The Teaching Of Efl In Venezuelamentioning
confidence: 99%
See 1 more Smart Citation
“…Even though teachers' competence in the target language is a requirement to use CLT, researchers in the field (Crandall, 1999;Freeman, 1989;Tedick & Walker, 1995) have found that the education of EFL teachers tends to focus on theoretical pedagogical knowledge and on English language skills based on grammar, phonology, morphology, syntax, and lexicon of the language, and more recently in notions and functions. In this sense, it is not surprising that teacher education programs in Venezuela, for example, place a heavy emphasis on descriptive linguistics, i.e., the study of the language at the sentence level (Chaco´n, Alvarez, Brutt-Griffler, & Samimy, 2003), overlooking the social nature of language as a means of communication and interaction.…”
Section: The Teaching Of Efl In Venezuelamentioning
confidence: 99%
“…Some scholars (Brosh, 1996;Crandall, 1999;Lafayette, 1993;Lange, 1990) argue against the pervasive tendency in many foreign language teacher education programs to view language as an ''object'' (Tedick & Walker, 1995) where instruction often becomes fragmented, decontextualized, teacher-centered, and separated from students' needs and interests (Cullen, 1994). As a result, generally teachers in Venezuela, for instance, may not acquire the communicative competence to perform in the four language skills: speaking, listening, reading, and writing.…”
Section: The Teaching Of Efl In Venezuelamentioning
confidence: 99%
“…Teacher knowledge implies that what is known is special to teachers as a group, but the term teaching knowledge is a type of knowledge related to the activities of teaching (Buchmann, 1986). As Freeman (1989) and Tedick and Walker (1995) indicated, the education of an English as a foreign language (EFL) teacher is a specialized case: it tends to focus on theoretical pedagogical knowledge and on English language skills based in grammar, phonology, morphology, syntax, and lexicon of the language. Without this content knowledge, it is not possible for language teachers to judge themselves competent enough to master language skills successfully.…”
Section: Teaching Knowledge and Competencymentioning
confidence: 98%
“…Tedick and Walker (1995) support the promotion of knowledge of the target culture and believe that language is often viewed as object in the classroom, which denies the social nature of language as communication and this view reduces language teaching to a narrow focus on parts and pieces. "Language study is generally decontextualised, unrelated to the lives of students, their school, or the community, and much of language instruction remains grammar-driven and primarily teacher-directed" (Tedick & Walker 1995: 501).…”
Section: Teacher Knowledgementioning
confidence: 99%